Islam dan Kearifan Lokal di Sulawesi Selatan Pasca Islamisasi - Muhaemin Elmahady (Hikmah: Journal of Islamic Studies, 2011)
The main source of the history of South Sulawesi is lontara’ including the historical development of Islam. Some manuscripts of lontara that provide information about the process of Islamization in South Sulawesi are: Lontara Bilang Gowa Tallo, Lontara’ Sukku’na Wajo and some others. The manuscripts also describe the fusion of custom norms called panngadakkang/ pangadereng with the norms of religion called sara’. Custom values get the same position with the religious values. Violations of the norms of religion are regarded as violations of the norms of custom. Integration of Islamic teachings into the custom and people’s lives led to the joints of the custom and people’s lives besides sara’ there are also ada’, rapang, wari’, and bicara. The example of custom that is held firmly is matanre siri’, which means having a high sense of shame and morality. Matanre siri’ is one of the requirements that must be owned by a leader. Having a sense of shame and noble character in Islam becomes the main mission of the Prophet, even having a sense of shame is part of one’s faith. The intermingling between the values of Islam and the local custom takes place throughout the region of South Sulawesi. As in Luwu, the structure of Palopo ancient city is still dominated by the influence of the local culture. This proves that the presence of Islam does not change the total socio-cultural images that have established. The reality shows that Islam just deconstructs the local culture to be accordance with Islamic aqidah (faith) and law according to al-Qur’ān and Hadith. Keywords: custom, lontara, norm, local policy Sumber informasi utama sejarah Sulawesi Selatan adalah lontara’, termasuk sejarah perkembangan Islam. Beberapa naskah lontara yang dapat memberikan tentang proses Islamisasi di Sulawesi Selatan antara lain: Lontara Bilang Gowa Tallo, Lontara’ Sukku’na Wajo, dan beberapa naskah lontara lainnya. Termasuk didalamnya digambarkan bagaimana terjadinya peleburan norma-norma adat yang disebut pangadakkang/ pangadereng dengan norma-norma agama yang disebut sara’. Nilai-nilai adat menjadi setingkat dengan agama. Pelanggaran terhadap norma-norma agama akhirnya identik dengan pelanggaran terhadap adat. Integrasi ajaran Islam ke dalam adat istiadat dan kehidupan masyarakat menyebabkan sendi-sendi adat-istiadat dan kehidupan masyarakat selain sara’ ada pula ada’, rapang, wari’, dan bicara. Contoh adat yang dipegang kokoh adalah matanre siri’ yang berarti mempunyai rasa malu yang tinggi dan berakhlak mulia. Matanre siri’ ini merupakan salah satu persyaratan yang harus dimiliki oleh seorang pemimpin. Rasa Malu dan akhlak mulia dalam Islam menjadi misi utama Rasulullah Saw, bahkan mempunyai rasa malu adalah bagian dari Iman seseorang. Pembauran antara nilai-nilai Islam dengan adat local berlangsung merata di wilayah Sulawesi Selatan. Seperti di daerah luwu, struktur kota kuno Palopo masih didominasi pengaruh budaya lokal. Hal ini membuktikan bahwa kehadiran Islam tidak merubah secara total citra-citra sosial budaya yang telah mapan. Kenyataan menunjukkan, Islam hanya melakukan dekonstruksi budaya lokal sejauh sesuai aqidah dan syariah menurut al-Qur’an dan Hadits Kata Kunci: adat, lontara, norma, kebijakan lokal